Ledipasvir and sofosbuvir in patients with genotype 1 hepatitis C virus infection and compensated cirrhosis: An integrated safety and efficacy analysis. Issue 1 (9th May 2015) - Reddy, K. Rajender; Bourlière, Marc; Sulkowski, Mark; Omata, Masao; Zeuzem, Stefan; Feld, Jordan J.; Lawitz, Eric; Marcellin, Patrick; Welzel, Tania M.; Hyland, Robert; Ding, Xiao; Yang, Jenny; et al.
Abstract : Patients with hepatitis C virus (HCV) infection and cirrhosis are underrepresented in clinical trials of interferon‐free regimens of direct‐acting antiviral agents, making it difficult to optimize therapy. We performed a post‐hoc analysis of data from seven clinical trials to evaluate the efficacy and safety of the fixed‐dose combination of ledipasvir (LDV) and sofosbuvir (SOF), with and without ribavirin (RBV), in 513 treatment‐naïve and previously treated patients with genotype 1 HCV and compensated cirrhosis. All patients received LDV‐SOF for 12 or 24 weeks with or without RBV. We determined the rates of sustained virological response (SVR) 12 weeks after treatment (SVR12) overall and for subgroups. Of the 513 patients analyzed, 69% were previously treated and 47% had failed previous treatment with a protease‐inhibitor regimen. Overall, 493 patients (96%; 95% confidence interval [CI]: 94%‐98%) achieved SVR12, 98% of treatment‐naïve and 95% of previously treated patients. SVR12 rates did not vary greatly by treatment duration (95% of patients receiving 12 weeks and 98% of patients receiving 24 weeks of treatment), nor by addition of RBV (95% of patients receiving LDV‐SOF alone and 97% of those who received LDV‐SOF plus RBV), although previously treated patients receiving 12 weeks of LDV‐SOF without RBV had an SVR12 rate of 90%. One patient discontinued LDV‐SOF because of an adverse event (AE). The most common AEs were headache (23%), fatigue (16%‐19%), and asthenia (14%‐16%). One patient (<1%) of those receiving LDV‐SOF alone, and 4 (2%) of those receiving LDV‐SOF plus RBV had treatment‐related serious AEs. Conclusions: This analysis suggests that 12 weeks of LDV‐SOF is safe and effective for treatment‐naïve patients with HCV genotype 1 and compensated cirrhosis. The relatively lower SVR in treatment‐experienced patients treated with 12 weeks of LDV‐SOF raises the question of whether these patients would benefit from adding RBV or extending treatment duration to 24 weeks. (Hepatology 2015;62:79‐86)